Oral alterations associated to gastroesophageal reflux disease - Yulisa Otero Baxter; Carlos Jesús Llapur Almaguer; Maritza Osorio Nuñez; Edelis Raimundo Padrón (Revista Cubana de Estomatología, 2020)
Introduction: Gastroesophageal reflux disease is a functional multifactorial disorder of the upper gastrointestinal tract. Oral alterations are considered to be extraesophageal manifestations of this disease.